Transformasi Digital: Menggali Potensi Teknologi Terkini Dalam Pengelolaan Dokumen Dan Informasi Kantor Pada Perusahaan PT. Victory Prima Abadi - Mochammad Zulvikri; Agnia Amani (Jurnal Transformasi Bisnis Digital, 2024)
Digital transformation has become an important paradigm shift in the management of office documents and information in the modern era. This article discusses the application of the latest technology in the management of office documents and information, specifically in the company PT Victory Prima Abadi. Through this case study, we will see how the company explores the potential of digital technology to improve efficiency and productivity in their operations. By integrating various technology solutions such as financial program applications, a digital attendance system, and the use of Microsoft Excel for document management, the company has made strides towards more efficient document management. However, challenges remain, especially in dealing with the aspect of archive storage that still relies on manual methods. This article aims to explore the company's efforts in utilizing analytics and artificial intelligence technologies to improve efficiency in the archive shrinkage process and identification of documents that require long-term storage. The results show that the utilization of digital technology in document and office information management has had a significant positive impact and has become a key element in the company's strategy to achieve future operational success. By continuing to develop and implement appropriate technology solutions, companies can further optimize document and information management and prepare for the challenges and opportunities of an increasingly connected and rapidly changing business world.